2018
DOI: 10.1002/jobm.201800204
|View full text |Cite
|
Sign up to set email alerts
|

Transposons: the agents of antibiotic resistance in bacteria

Abstract: Transposons are a group of mobile genetic elements that are defined as a DNA sequence. Transposons can jump into different places of the genome; for this reason, they are called jumping genes. However, some transposons are always kept at the insertion site in the genome. Most transposons are inactivated and as a result, cannot move. Transposons are divided into two main groups: retrotransposons (class І) and DNA transposons (class ІІ). Retrotransposons are often found in eukaryotes. DNA transposons can be foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 139 publications
1
90
0
11
Order By: Relevance
“…Transposases are proteins encoded by transposons that allows the transposons to move from plasmid to chromosome or vice versa and could carry antibiotic resistant gene payload [52,53]. Interestingly, after treatment with cipro a significant jump in the relative abundance of transposases was observed and could signify an increased potential for horizontal gene transfer in the gut community of cipro treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transposases are proteins encoded by transposons that allows the transposons to move from plasmid to chromosome or vice versa and could carry antibiotic resistant gene payload [52,53]. Interestingly, after treatment with cipro a significant jump in the relative abundance of transposases was observed and could signify an increased potential for horizontal gene transfer in the gut community of cipro treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…A heatmap was created for each antibiotic using R with ggplot2 package to demonstrate clustering of samples based on the similarity of compositional species profiles (log-transformed relative abundance across all identified species). Hierarchical clustering was performed and a dendrogram was created using unweighted pair group mean with arithmetic mean (UPGMA) algorithm (53,54,55). The order of the listed bacterial species in each heatmap of the Fig.…”
Section: Taxonomic Analysismentioning
confidence: 99%
“…Xue et al (42) showed that exogenous AI-2 increased the antibiotic resistance of clinical E. coli strains isolated from cow's papillitis by upregulating the expression of TEM-type enzyme in an LsrR-dependent manner. Transposons are a group of mobile genetic elements that are defined as a DNA sequence (43). Because of its ability to move between bacterial chromosomes, plasmids, and phages, resistance on the transposon is more easily transmitted and disseminated horizontally (44,45).…”
Section: Luxs/ai-2 Qs System Contributes To Antibiotic Resistancementioning
confidence: 99%
“…If not diagnosed in time and treated properly, UTIs increase the economic burden and are associated with severe and serious acute and chronic consequences that include recurrence, pyelonephritis with sepsis, renal damage, preterm birth, and complications (Flores-Mireles et al, 2015). Treatment of bacterial infection has become difficult due to drug resistance (Babakhani & Oloomi, 2018). Moreover, catheter-associated UTIs have higher risk of mortality (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%